Impact of antimicrobial resistance in production animals: A literature review (Research, Society and Development, 2024)
Antimicrobial resistance (AMR) is a growing challenge in veterinary medicine and public health, exacerbated by the excessive or inappropriate use of antimicrobials in farm animals. The aim of this study is to investigate the effects of antimicrobial resistance (AMR) in farm animals. The use of antimicrobials and the consequences of bacterial resistance in livestock production are examined in this study. The methodology involved searching scientific articles, reviews and reports in databases such as PubMed, Scielo and ScienceDirect to focus on keywords related to antimicrobial use and bacterial resistance. International regulations and research carried out by organizations such as the WHO and the OIE were included. The results show that the indiscriminate use of antimicrobials in animals, whether for treatment, prevention or growth promotion, leads to the development of resistant strains, which make it difficult to treat infections. Antimicrobial resistance is a problem in Brazil in dairy, poultry and pig production. Alternative products to antimicrobials, such as probiotics and herbal medicines, are being studied to minimize the effects of AMR without harming productivity. The discovery of resistance mechanisms and the control of pathogen propagation are facilitated by technologies such as Whole Genome Sequencing (WGS). AMR is a growing challenge that requires strict regulations, proper management practices and the development of new technologies to ensure public health and food safety.